Literature Study Related to Factors Affecting Fraud Detection: Audit Risk, Investigative Audit Techniques, and Whistleblowing System - Ependi, Hendi; Nugrahanti, Trinandari Prasetya (West Science Business and Management, 2024)
Fraud detection is a crucial aspect in auditing that aims to protect the integrity and reliability of financial statements. This study aims to review the main factors that influence the effectiveness of fraud detection, namely audit risk, investigative audit techniques, and whistleblowing systems. Based on the literature, these three factors play a significant role in improving the auditor's ability to detect fraud. Audit risk helps auditors focus on areas with higher potential for fraud, investigative audit techniques allow auditors to dig deeper into suspected fraud, while whistleblowing systems serve as early warning tools. This study provides in-depth insights for organizations regarding the importance of implementing these three factors in strengthening internal control and audit.